Effects of English pronunciation instruction and the exploration of social values with second-graders. (2025)
This research study explores the effects of English pronunciation instruction while exploring social values with a group of second-grade students from a public school at Bogotá. By recognizing the lack of pronunciation instruction time within the EFL classroom while integrated with social values, the study aims to highlight the importance of fostering a critical perspective on language teaching and learning that consider both linguistic and social development. Through an action research approach, a series of classroom interventions were designed to develop pronunciation skills and to promote social values within students, such as self-esteem, teamwork and respect. Following a grounded theory approach, the analysis of data collected through field diaries and a questionnaire, reveals that explicit pronunciation instruction helps students become more aware of their oral production and, the integration of values created a respectful learning environment for themselves and others. This study supports the idea that pronunciation instruction in early education should be addressed critically to reflect both linguistic and social dimensions of language learning.